A Comparison of the Ability of Some Commercially Produced Biological Control Agents to Protect Strawberry Plants against the Plant Pathogen Phytophthora cactorum - Matěj Pánek (MDPI AG, 2021)
A comparison of the ability of commercially produced biological control agents—Contans, Gliorex, Hirundo, Polyversum, Prometheus, Clonoplus, Integral Pro and Xilon GR, completed with an isolate of Clonostachys rosea and of Pseudomonas sp.—to protect strawberry plants against Phytophthora cactorum was performed. The experiment was performed on strawberry cultivars Sonata, Karmen, and Wendy—cultivated in a cultivating room and greenhouse. The health of plants was affected negatively by the pathogen in all variants of biological agents used, but differences were seen in the rates of this decrease. The results revealed the ability of some tested agents to improve the growth of plants in the absence of the pathogen; the preparation Polyversum (Pythium oligandrum) was the most beneficial, in both the presence and absence of the pathogen. Contrarily, some agents alone decreased the health of plants; Integral Pro (Bacillus subtillis) and a strain of Pseudomonas sp. caused a deterioration in the health of the plants, even in the absence of a pathogen. The results of our analysis demonstrate the varied usefulness of all agents under unified environmental conditions; their effect seems to be dependent on the conditions and on the combination of the genotypes of all three participants in the interaction: plant–pathogen–antagonist.